PENGARUH PENGGUNAAN MEDIA KARTU HURUF UNTUK MENGATASI KESULITAN MEMBACA HURUF PADA ANAK PEKERJA MIGRAN INDONESIA FASE A DI MALAYSIA - Rina Diana; Iwan Kuswandi; Zainuddin (STKIP Subang, 2024)
This study is based on the problem of difficulties in reading letters experienced by phase A Indonesian Migrant Worker children in Malaysia. This happens because of the lack of learning media that can support learning activities. With this problem, the purpose of this study is to identify the effect of letter card media in overcoming difficulties in reading letters in Phase A Indonesian Migrant Worker children in Malaysia. Immigrant children often face language barriers that affect their literacy skills, including letter recognition. Letter card media as a visual and interactive learning tool is expected to facilitate the learning process of reading letters effectively. The type of research used is quantitative research with data collection techniques using pretest and posttest, as well as observation of learning activities, teacher and student interviews, and documentation as a supporting tool and can be used as an archive as evidence of research implementation. The results showed that the use of letter card media was significantly able to improve the ability to read letters in Indonesian Migrant Worker children which can be seen from the results of data analysis tests using normality tests, homogeneity tests, and t tests. The t test results showed a significance value of 0.000 (p < 0.05), which means the hypothesis is accepted. This media not only attracts children's interest in learning, but also helps them to understand the importance of learning.